Innovation spillovers as a driver of economic development: evidence from regions located in Central and Eastern European Union countries - Grodzicki, Tomasz; Jankiewicz, Mateusz (Technological and Economic Development of Economy, 2025)
Innovation has been a core element in the economic development of countries worldwide. Although innovation often has a global impact, it is created in a particular location. This research focuses on regions from Central and Eastern European Union (EU) countries as they are in the process of catching up with more developed Western EU economies. This paper aims to explore the link between innovation level and economic development in Central and Eastern EU countries from a regional perspective as well as to examine the impact of innovation spread between these regions. The analysis applies spatio-temporal models for data on the regional innovation index and gross domestic product per capita from 2016 to 2022. The results of this research show that southeastern regions had, on average, a lower level of both innovation and economic growth than western and northern ones. The analysis also confirms the positive relationship between innovation and economic development in these regions. Finally, this research proves the existence of spatial innovation spillovers: the strongest effect in Polish (near its capital city’s region) and Romanian regions while the weakest one in Slovenia, Bulgaria, and further from the capitals of Romania, Poland, and the Czech Republic.First published online 16 July 2025